144 Nurses meet the challenge of helping high CVD risk smokers to quit with the help of varenicline in a preventive cardiology programme. (16th May 2012) - Jennings, C S; Kotseva, K; De Bacquer, D; Hoes, A; De Velasco, J; Brusaferro, S; Tonstad, S; Wood, D A
Abstract : Background: The EUROACTION plus study aimed to assess effectiveness of a nurse-led preventive cardiology programme for high CVD risk smokers willing to make a quit smoking attempt compared to usual care in general practice. Methods: High CVD risk smokers aged to 18–80 years with vascular disease and 50–80 years at high risk of developing CVD (Heartscore ≥5% over 10 years, or treated for risk factors or DM) and their partners were individually randomised to either the programme (EA+) or usual care (UC). EA+ patients had optional access to free varenicline and met with the study nurse every 2 weeks to support their quit attempt and to have dietary and physical activity advice and CVD risk factor management. The primary outcome was self reported 7-day point prevalence of abstinence validated with breath carbon monoxide of <10 ppm. Analysis was by intention to treat (ITT). Follow-up was at 16 weeks. Results: 696 patients were recruited: 350 randomised to EA+ and 346 to UC. 85% EA+ and 83% UC returned at 16 weeks. 91% of patients in EA+ chose to use varenicline to help them to quit smoking and 51% of EA+ patients quit compared to 19% in UC (OR 4.52 95% CI 3.2 to 6.4 p<0.0001). In those who fully participated in EA+ 63% quit smoking compared to 17% who did not complete and 22% who did not participate. At follow-up self reported health related quality of life (HRQoL) was better in EA+ with significantly higher mean EQ-VAS scores in EA+ (74/100) compared to UC (70, p=0.002). Functional limitation profile scores (SF36) improved in EA+ during the programme (25.6−26.2 ∆ +0.56 95% CI 0.23 to 0.88 p=0.0009). No differences were seen in depression scores (HADS), but anxiety scores reduced in EA+ during the programme (5.63−5.27 ∆ −0.35 95% CI −0.67 to −0.03 p=0.03). Conclusion: Intensive support from nurses with optional use of varenicline was successful in helping over half of all high CVD risk smokers to quit. This was associated with a reduction in anxiety and increased quality of life.